2011
DOI: 10.1111/j.1939-165x.2011.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Grey eosinophils in sighthounds: frequency in 3 breeds and comparison of eosinophil counts determined manually and with 2 hematology analyzers

Abstract: GE are found in the blood of sighthounds other than Greyhounds. Hematology analyzers may underestimate the percentage of GE, probably due to their abnormal physical or chemical features. Underestimation is slight and usually clinically insignificant, but occasionally eosinophils are completely misclassified. Using the Sysmex analyzer, a GE gate can be designed to normalize the eosinophil count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…These eosinophils are not associated with clinical disease and do not represent functional changes (Iazbik & Couto , Giori et al . ). Proposed causes include alteration in basic proteins in the granules or a decrease in pH of the granules, resulting in less binding of the eosin stain (Iazbik & Couto , Zaldívar‐López et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These eosinophils are not associated with clinical disease and do not represent functional changes (Iazbik & Couto , Giori et al . ). Proposed causes include alteration in basic proteins in the granules or a decrease in pH of the granules, resulting in less binding of the eosin stain (Iazbik & Couto , Zaldívar‐López et al .…”
Section: Discussionmentioning
confidence: 97%
“…One study found that two separate automated analysers significantly underestimated eosinophil counts in dogs with grey eosinophils when compared to manual counts; however, the analysers were consistent with manual counts in dogs with normal staining eosinophils (Giori et al . ). Some of the deerhounds in this study had eosinophil counts that appeared to be underestimated by the analyser when compared to manual cell counts and this was more frequent in dogs with grey eosinophils; however, further studies on eosinophil morphology and its effect on automated analysers are needed to determine if this is clinically relevant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, another consequence of breed‐related differences for hematology is the result of technical difficulties affecting performance of the analyzers. The presence of grey eosinophils in sighthounds, for example, may lead to underestimation of the eosinophil counts …”
mentioning
confidence: 91%
“…Sighthounds have unique physiologic adaptations, likely due to selective breeding over the centuries for hunting and racing, which result in laboratory values that are outside reference intervals established for the general population of dogs. Different studies in several sighthound breeds have shown differences in haematological profiles, electrolyte concentrations, blood gas values, prevalence of dog erythrocyte antigens and serum biochemical profiles compared with dogs of other breeds (Hilppo 1986;Steiss et al 2000;Iazbik et al 2010;Giori et al 2011;Zaldívar-López et al 2011a, b;Uhrikova et al 2013;Sheerer et al 2013). Although several studies have reported differences in total proteins and total globulins in sighthounds (Porter and Canaday 1971;Hilppo 1986;Steiss et al 2000;Uhrikova et al 2013;Sheerer et al 2013), to the authors' knowledge, only one research has been published in serum protein electrophoresis; Fayos et al (2005) showed significantly lower total serum globulins in Greyhounds owing to decreases in the α-and β-globulin fractions compared with dogs of other breeds.…”
Section: Introductionmentioning
confidence: 98%